1958
DOI: 10.1152/ajplegacy.1958.194.3.590
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Ventricular Arrhythmias and Myocardial Fatty Changes After Large Doses of Norepinephrine and Epinephrine in Unanesthetized Dogs

Abstract: An intravenous infusion of a large dose (0.51 mg/kg) of norepinephrine sensitizes the heart to the action of catechol amines for a period of 2–4 days. During this period, small doses of either epinephrine or norepinephrine induce ventricular tachycardia. In dogs killed the day after infusion, frozen sections of the myocardium stained with Oil red O reveal fatty changes, the severity of which roughly parallels that of the induced tachycardias. Fatty changes were still present in the hearts of dogs killed the 3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Watts and others 9 " 14 have recently shown that arterial epinephrine levels rise sharply during hemorrhagic hypotension. Maling and others 15 " 18 have observed subendocardial hemorrhages following infusion of relatively large quantities of epinephrine and norepinephrine, while similar lesions have been reported by Wartman et al 19 following occlusion of the main coronary arterial supply to the left ventricle.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Watts and others 9 " 14 have recently shown that arterial epinephrine levels rise sharply during hemorrhagic hypotension. Maling and others 15 " 18 have observed subendocardial hemorrhages following infusion of relatively large quantities of epinephrine and norepinephrine, while similar lesions have been reported by Wartman et al 19 following occlusion of the main coronary arterial supply to the left ventricle.…”
supporting
confidence: 56%
“…of epinephrine in confirmation of the earlier studies of Freeman et al 28 Again, autopsy findings were not reported. The infusion levels of Maling and Highman 15 (2.1 to 6.2 /ig./Kg./min. ), which produced pathological changes in the myocardium, were in a comparable range.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent increase in cardiac lipidosis which occurred as a result of fat loading of the diet, and the vastly accen tuated effect of saturated animal fats, a direct link between the accumulation of fat droplets in the muscles of the heart and the onset or severity of cardiac necrosis or its pathological sequelae have not been unequivocally dem onstrated [27,43]. However, in view of the high incidence of both dysrhythmia and asso ciated lipidosis in the myocardium of rats fed an animal-fat-supplemented diet, it should be noted that earlier studies have reported an association between lipid accumulation and electrophysiological disturbances and ar rhythmias [44,45], Our findings therefore confirm and extend our preliminary reports [21,31] that dietary lipids can act as powerful modulators of car diac responses to inotropic agents, and suggest that long-term ingestion of polyunsaturated fats of vegetable origin may have a significant role in the prevention or reduction in severity of coronary heart disease. Similar observa tions with alternative species to rats would greatly increase the potential relevance of these findings to human nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Fat infiltration of the liver and myocardium is observed after burns (Sevitt, 1962) and after multiple injuries complicated by peritonitis. Experimentally, catecholamines are capable of inducing fatty change in various tissues (MacKay, 1937;Aujard, 1953;Maling & Highman, 1958;Fiegelson et al, 1961).…”
Section: Introductionmentioning
confidence: 99%